2008
DOI: 10.1007/s11430-008-6004-y
|View full text |Cite
|
Sign up to set email alerts
|

Propagation characteristics of converted refracted wave and its application in static correction of converted wave

Abstract: Three-component seismic exploration through P-wave source and three-component geophone is an effective technique used in complicated reservoir exploration. In three-component seismic exploration data processing, one of the difficulties is static correction of converted wave. This paper analyzes propagation characteristics of non-converted and converted refracted waves, and discovers a favorable condition for the formation of converted refracted wave, i.e. the velocity of overlaying medium S wave is much lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Generally speaking, S-wave statics is far greater than Pwave's, the relevance of them is very small. According to Hall's description of kinematical feature of the converted-refraction and non convertedrefraction [15] and Liu's quantitative analysis for PPS converted-refraction [20] , P-wave refraction will be converted to S-wave at the bottom of weathering (that is Fig. 1 The geometry relationship of upgoing P-and S-wave travel in the near surface top of HVL) due to strong S-wave velocity contrast, the majority energy will be recorded by horizontal component (Fig.…”
Section: Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, S-wave statics is far greater than Pwave's, the relevance of them is very small. According to Hall's description of kinematical feature of the converted-refraction and non convertedrefraction [15] and Liu's quantitative analysis for PPS converted-refraction [20] , P-wave refraction will be converted to S-wave at the bottom of weathering (that is Fig. 1 The geometry relationship of upgoing P-and S-wave travel in the near surface top of HVL) due to strong S-wave velocity contrast, the majority energy will be recorded by horizontal component (Fig.…”
Section: Methodologiesmentioning
confidence: 99%
“…Most of recent literatures are involved in non converted-refraction (PPP and SSS mode) [16−19] , and converted-refraction is rarely mentioned. Liu [20] gave an overall analysis for converted-refraction's propagation law and characterization, he pointed out that the favorable condition for generating converted-refraction is that the upper layer velocity is far less than lower layer's, he derived S-wave delay-time from converted-refraction and then S-wave statics are obtained. This paper gives a detailed derivation for accurate S-wave statics utilizing the PPP and PPS mode refraction, involved velocity ratios are only regional values which constrain the calculation.…”
Section: Introductionmentioning
confidence: 99%
“…Addy et al (2005) have studied Rayleigh waves in a viscoelastic half-space under initial hydrostatic stress in presence of the temperature field. Liu et al (2008) have demonstrated the propagation characteristics of converted refracted wave and its application in static correction of converted wave. Moczo et al (2007) provided mathematical modeling of seismic wave propagation using the Finite-Difference time-domain method.…”
Section: Introductionmentioning
confidence: 99%
“…This cannot be guaranteed. Arguably more justifiable are approaches which analyse horizon-timing differences on common-receiver-gathers (CRGs) (Cary and Eaton, 1993), or methods using PPS and SSS refractions (Houston et al, 1989;Liu and Wei, 2008). More recent areas of study include a technique based on correlation of adjacent CRGs (Guevara et al, 2015); ray-path interferometry via the radial trace or Tau-p domains (e.g.…”
mentioning
confidence: 99%